Application of high‐throughput single nucleotide polymorphism genotyping for assessing the origin of Engraulis encrasicolus eggs. Issue 7 (1st June 2020) - Catanese, Gaetano; Di Capua, Iole; Iriondo, Mikel; Bonanno, Angelo; Estonba, Andone; Procaccini, Gabriele
Abstract: Single nucleotide polymorphism (SNP) markers in anchovy ( Engraulis encrasicolus ) egg samples were analysed to detect their origin on a small spatial scale (200 km) by assigning genotypes to adult anchovy stocks. The novelty of this work is the application of a rapid high‐throughput method for genotyping each single anchovy egg, in a single execution, using a set of 96 genome‐wide SNPs in a dynamic array system with microfluidic technology (Fluidigm 96.96). The existence of two ecotypes in E. encrasicolus had already been identified based on SNP polymorphism in the Atlantic Ocean and in the Mediterranean Sea, showing that habitat type (offshore versus coastal/estuarine) is the most important component of genetic differentiation among populations of anchovy. In this work, anchovy egg genotypes from areas of the Western Mediterranean were assigned to adult populations. Only two localities in which adult anchovies were sampled represented donor populations for the coastal/estuarine egg genotypes. Although some degree of mixing among the hauls could exist, the assignment of egg groups to adult populations led to distinguishing the contributions of distinct ecotypes to new wild generations. We can conclude that the high rate of egg dispersion caused by marine currents and the different degrees of local retention could explain the genetic heterogeneity observed in the adult populations, where eggs from neighbouring spawning sites tend to mix. The results highlight that this technique represents a new and useful tool for addressing evolutionary questions, breed recognition, assignment, and connectivity assessment of individual eggs, and anchovy population dynamics, for the management of stocks.